Effects of matcha green tea on the pharmacokinetics of nadolol in rats - Eslam T. Mashaqbeh; Tamam El-Elimat; Osama Y. Alshogran; Iyad Hamzeh; Zahraa M. Obeidat; Ahmed H. Al Sharie; Feras El Hajji (PLoS ONE, 2026)
The concurrent use of herbal dietary supplements with prescription medications raises safety concerns due to the potential for clinically significant interactions. Matcha, a shade-grown green tea consumed as an ultra-fine powder, is rich in catechins that may inhibit the transport of P-glycoprotein (P-gp) substrates such as nadolol. This study investigated the effects of administering single and multiple doses of matcha on the pharmacokinetics of nadolol in an in vivo animal model. Male Sprague-Dawley rats ( n = 32) were randomly assigned to four groups. Group 1 (negative control) was administered normal saline followed by a single oral dose of nadolol (10 mg/kg). Group 2 (matcha single-dose) was administered a single dose of matcha (250 mg/kg) whisked in normal saline, followed by nadolol (10 mg/kg) after 30 min. Group 3 (positive control) received itraconazole (50 mg/kg), followed by nadolol (10 mg/kg) after 30 min. Group 4 (matcha multiple-dose) received matcha (250 mg/kg daily for 21 days) before administering nadolol (10 mg/kg) on day 21. Blood samples were collected at 0, 0.33, 0.66, 1, 1.5, 2, 3, 4, 5, 8 and 24 h. Nadolol concentrations in plasma were measured by a validated high-performance liquid chromatography with fluorescence detection (HPLC-FL) method. Pharmacokinetic parameters were estimated using the PK solver add-in for Microsoft Excel. To ensure quality control, caffeine, a key marker compound of matcha green tea, was quantified using HPLC with ultraviolet detection (HPLC-UV). A single oral dosage of matcha (250 mg/kg) had no statistically significant effects on the pharmacokinetics of nadolol compared to the control group ( p > .05). Although the multiple-dose matcha group showed an increase in C max (~45%), AUC 0-t (~18%), and AUC 0-∞ (~22%) for nadolol compared to the control group, these differences were not statistically significant ( p > .05). In contrast, the t ½ (h) of nadolol increased significantly from 4.0 ± 1.6 in the control group to 7.7 ± 4.2 ( p = .039) in the matcha multiple-dose group. Itraconazole co-administration significantly increased systemic exposure (AUC) of nadolol ( p = .009), confirming the validity of the animal model. Caffeine, a key marker compound in matcha tea, was quantified at 4.18 ± 0.44% w/w of dry matcha tea powder, equivalent to 41.8 ± 4.4 mg/g. This is the first study to explore the potential pharmacokinetic interaction between matcha tea and nadolol. Single and multiple oral doses of matcha green tea had negligible effects on most pharmacokinetic parameters of nadolol, except for an increased half-life in the multiple-dose group. Further research is needed to establish the clinical relevance of this interaction before definitive recommendations on the safety of matcha tea and nadolol coadministration can be made.